Performance Analysis of Dijkstra-Based Weighted Sum Minimization Routing Algorithm for Wireless Mesh Networks. (6th May 2014) - Alwan, Nuha A. S.
Abstract : Multiobjective optimization methods for routing in static wireless mesh networks (WMNs), with more than one QoS measure to be optimized, are highly challenging. To optimize the performance for a given end-to-end route in a static network, the most common metrics that need to be optimized or bounded are the path capacity and the end-to-end delay. In this work, we focus on combining desirable properties of these two metrics by minimizing a weighted metrics sum via a Dijkstra-based algorithm. The approach is directed towards fast convergence rather than optimality. It is shown that the resulting algorithm provides more satisfactory results than simple Dijkstra-based pruning algorithms in terms of simultaneously achieving high capacity and small delay. The effect of changing the weighting factor on the proposed algorithm performance is investigated.